\(2-\dfrac{8}{9}\)
\(\dfrac{5}{8}x3\)
\(5:\dfrac{6}{21}\)
Tính rồi rút gọn:
a) \(\dfrac{2}{9}+\dfrac{1}{9}\) b) \(\dfrac{5}{6}+\dfrac{1}{6}\) c) \(\dfrac{11}{8}-\dfrac{5}{8}\) d) \(\dfrac{5}{21}-\dfrac{2}{21}\)
\(\dfrac{21}{24}\)x\(\dfrac{2}{11}\):\(\dfrac{9}{8}\)=.......
\(\dfrac{17}{9}\)x\(\dfrac{5}{6}\):\(\dfrac{12}{13}\)=.......
\(\dfrac{21}{24}\cdot\dfrac{2}{11}:\dfrac{9}{8}=\dfrac{21}{24}\cdot\dfrac{2}{11}\cdot\dfrac{8}{9}=\dfrac{16}{99}\)
\(\dfrac{17}{9}\cdot\dfrac{5}{6}:\dfrac{12}{13}=\dfrac{17}{9}\cdot\dfrac{5}{6}\cdot\dfrac{13}{12}=\dfrac{1105}{648}\)
a)\(\dfrac{14}{99}\)
b)\(\dfrac{1105}{648}\)
6. ÉT O ÉT
\(\dfrac{9}{7}\) và \(\dfrac{5}{6}\) \(\dfrac{4}{7}\) và \(\dfrac{8}{21}\) \(\dfrac{2}{5};\dfrac{1}{3}\) và \(\dfrac{1}{2}\) \(\dfrac{1}{3};\dfrac{4}{3}\) và\(\dfrac{1}{5}\)
a: 9/7>1>5/6
b: 4/7=12/21>8/21
c: 2/5=12/30
1/3=10/30
1/2=15/30
mà 10<12<15
nên 1/3<2/5<1/2
Tìm x, biết:
a) \(\left(-\dfrac{5}{9}\right)^{10}\) : x = \(\left(\dfrac{-5}{9}\right)^8\)
b) x ; \(\left(\dfrac{-5}{9}\right)^8\) = \(\left(\dfrac{-9}{5}\right)^8\)
c) x3 = -8
a) (-5/9)^10 : x = (-5/9)^8
=> x = (-5/9)^10 : (-5/9)^8
=> x = (-5/9)^10-8 = (-5/9)^2
=> x = 25/81
b ) x : (-5/9)^8 = (-9/5)^8
=> x = (-9/5)^8 . (-5/9)^8
=> x = ( (-9)^8.(-5)^8 )/(5^8 . 9^8 )
=> x = 1
C) x^3 = -8 =(-2)^3
=> x = -2
a) (-5/9)¹⁰ : x = (-5/9)⁸
x = (-5/9)¹⁰ : (-5/9)⁸
x = (-5/9)²
x = 25/81
b) x : (-5/9)⁸ = (-9/5)⁸
x = (-9/5)⁸ . (-5/9)⁸
x = [-9/5 . (-5/9)]⁸
x = 1⁸
x = 1
c) x³ = -8
x³ = (-2)³
x = -2
a) \(\dfrac{-21}{15}\).\(\dfrac{-10}{14}\) b)\(\left(-\dfrac{2}{3}\right)^2\) c)\(\dfrac{-3}{4}\).\(\dfrac{-4}{5}\).\(\dfrac{16}{9}\) d)\(\dfrac{-8}{3}\).\(\dfrac{5}{6}\) e)\(\dfrac{16}{30}\).\(\dfrac{5}{12}\) f) \(\dfrac{13}{30}\).\(\dfrac{-1}{5}\) g)\(\dfrac{2}{21}\).\(\dfrac{3}{28}\) h)\(\left(\dfrac{-3}{4}\right)^3\)
`a, -21/15 . (-10)/14 = 210/210=1`
`b, (-2/3)^2= 4/9`
`c, (-3)/4 . (-4)/5 . 16/9= 192/180=16/15`
`d, (-8)/3 . 5/6= -40/18=-20/9`
`e, 16/30 . 5/12= 8/15 . 5/12=40/180=2/9`
`f, 13/30 . (-1)/5= -13/150`
`g, 2/21 . 3/28= 6/588= 1/98`
`h, (-3/4)^3= -27/64`
5. \(\dfrac{-3}{7}\) + \(\dfrac{5}{13}\) + \(\dfrac{-4}{12}\)
6. \(\dfrac{-5}{21}\) + \(\dfrac{-2}{21}\) + \(\dfrac{8}{24}\)
7. \(\dfrac{5}{13}\) + \(\dfrac{-5}{7}\) + \(\dfrac{-20}{41}\) + \(\dfrac{8}{13}\) + \(\dfrac{-21}{41}\)
Giúp tớ với ạ🥺👉🏻👈🏻 Tớ cảm ơn nhiều🥰
5.\(-\dfrac{3}{7}+\dfrac{5}{13}+\dfrac{-4}{12}=-\dfrac{103}{273}\)
b.\(-\dfrac{5}{21}+\dfrac{-2}{21}+\dfrac{8}{24}=\dfrac{-5-2}{21}+\dfrac{8}{24}=-\dfrac{7}{21}+\dfrac{8}{24}=-\dfrac{1}{3}+\dfrac{8}{24}=0\)
c.\(\dfrac{5}{13}+\dfrac{-5}{7}+\dfrac{-20}{41}+\dfrac{8}{13}+\dfrac{-21}{41}=\left(\dfrac{5}{13}+\dfrac{8}{13}\right)+\left(\dfrac{-20}{41}+\dfrac{-21}{41}\right)+-\dfrac{5}{7}=1-1-\dfrac{5}{7}=-\dfrac{5}{7}\)
\(a.\dfrac{3}{5}\) x \(\dfrac{17}{21}\) \(+ \) \(\dfrac{17}{21}\) x \(\dfrac{2}{5}\)
\(b.(\dfrac{8}{5}+\dfrac{5}{6}):\dfrac{7}{6}\)
`a)3/5xx17/21+17/21xx2/5`
`=17/21xx(3/5+2/5)`
`=17/21xx1=17/21`
`b)(8/5+5/6):7/6`
`=(48/30+25/30)xx6/7`
`=73/30xx6/7`
`=73/35`
\(a,\dfrac{3}{5}+\dfrac{-5}{9}\)
\(b,\dfrac{1}{3}+\dfrac{-4}{3};\dfrac{4}{7}\)
\(c,-\dfrac{27}{23}+\dfrac{5}{21}+\dfrac{4}{23}+\dfrac{16}{21}+\dfrac{1}{2}\)
\(d,\dfrac{-8}{9}+\dfrac{1}{9}.\dfrac{2}{9}+\dfrac{1}{9}.\dfrac{7}{9}\)
\(a,\dfrac{3}{5}+\dfrac{-5}{9}=\dfrac{27-25}{45}=\dfrac{2}{49}.\)
\(c,\dfrac{-27}{23}+\dfrac{5}{21}+\dfrac{4}{23}+\dfrac{16}{21}+\dfrac{1}{2}=\dfrac{-23}{23}+\dfrac{21}{21}+\dfrac{1}{2}=-1+1+\dfrac{1}{2}=\dfrac{1}{2}.\)
\(d,\dfrac{-8}{9}+\dfrac{1}{9}.\dfrac{2}{9}+\dfrac{1}{9}.\dfrac{7}{9}=\dfrac{-8}{9}+\dfrac{1}{9}.\left(\dfrac{2}{9}+\dfrac{7}{9}\right)=\dfrac{-8}{9}+\dfrac{1}{9}.1=\dfrac{-8+1}{9}=\dfrac{-7}{9}.\)
\(\dfrac{-5}{21}+(\dfrac{-16}{21}+1)\)
\(\dfrac{-3}{8}.\dfrac{1}{6}+\dfrac{3}{-8}.\dfrac{5}{6}+\dfrac{-10}{16}\)
a)
\(\dfrac{-5}{21}+\left(\dfrac{-16}{21}+1\right)=\dfrac{-5}{21}+\dfrac{-16}{21}+1\)=\(-1+1=0\)
`(-5)/21+((-16)/21+1)`
`=(-5)/21-16/21+1`
`=-1+1=0`
`(-3)/8*1/6+3/(-8)*5/6+(-1)/16`
`=-3/8*(1/6+5/6)-10/16`
`=-3/8-10/16`
`=-6/16-10/16=-16/16=-1`
\(\dfrac{-3}{8}.\dfrac{1}{6}+\dfrac{-3}{8}.\dfrac{5}{6}+\dfrac{-10}{16}\)
=\(\dfrac{-3}{8}.\left(\dfrac{1}{6}+\dfrac{5}{6}\right)+\dfrac{-10}{16}\)
=\(\dfrac{-3}{8}+\dfrac{-5}{8}=-1\)=